In-vivo magnetic resonance spectroscopy of lactate as a non-invasive biomarker of dichloroacetate activity in cancer and non-cancer central nervous system disorders - Kamson, David O.; Chinnasamy, Viveka; Grossman, Stuart A.; Bettegowda, Chetan; Barker, Peter B.; Stacpoole, Peter W.; Oeltzschner, Georg (Frontiers in Oncology, 2023)
The adverse effects of lactic acidosis in the cancer microenvironment have been increasingly recognized. Dichloroacetate (DCA) is an orally bioavailable, blood brain barrier penetrable drug that has been extensively studied in the treatment of mitochondrial neurologic conditions to reduce lactate production. Due to its effect reversing aerobic glycolysis (i.e., Warburg-effect) and thus lactic acidosis, DCA became a drug of interest in cancer as well. Magnetic resonance spectroscopy (MRS) is a well-established, non-invasive technique that allows detection of prominent metabolic changes, such as shifts in lactate or glutamate levels. Thus, MRS is a potential radiographic biomarker to allow spatial and temporal mapping of DCA treatment. In this systematic literature review, we gathered the available evidence on the use of various MRS techniques to track metabolic changes after DCA administration in neurologic and oncologic disorders. We included in vitro, animal, and human studies. Evidence confirms that DCA has substantial effects on lactate and glutamate levels in neurologic and oncologic disease, which are detectable by both experimental and routine clinical MRS approaches. Data from mitochondrial diseases show slower lactate changes in the central nervous system (CNS) that correlate better with clinical function compared to blood. This difference is most striking in focal impairments of lactate metabolism suggesting that MRS might provide data not captured by solely monitoring blood. In summary, our findings corroborate the feasibility of MRS as a pharmacokinetic/pharmacodynamic biomarker of DCA delivery in the CNS, that is ready to be integrated into currently ongoing and future human clinical trials using DCA.